First record of the genus Morophaga Herrich-Schäffer (Lepidoptera, Tineidae) from the Ogasawara Islands, Japan, with a new species - Jinhyeong Park; Sadahisa Yagi; Toshiya Hirowatari (Nota Lepidopterologica)
The present study records Morophaga formosana Robinson, 1986 and describes M. hahajimana sp. nov. from the Ogasawara Islands of Japan. This is the first record of this genus Morophaga Herrich-Schäffer, 1853 (Tineidae) from the Oceanian region. Photographs of adult specimens, wing veins, genitalia, and larval biology are presented. We have constructed a preliminary phylogenetic tree based on cytochrome c oxidase subunit I (COI-5P) DNA barcode sequences, including those of some Scardiinae species.